NEO Smart Fans / Ainur Asyirah … [et al.] - -, Ainur Asyirah; -, Jasmine Aimi; -, Batrisyia Aleeyah; Abas, Norlela (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
In this current era of technology, there is still a lack of high-tech invention towards certain home appliances such as fans. To develop all the products with high-tech features, we need to use all the technology sources effectively to reach the expectation hence facilitating all the users for a better life. Therefore, we invent new high-tech fans with the aim to be the brand with the best environmentally friendly product that brings convenience to the consumer. Many manufacturers focus on the shape and design of their products to attract customers. There are very few manufacturers that focus on the configuration of their products. Thus, compared to other manufacturers, our product focuses on the configuration where we make sure that our product is using the best high-tech features with various smart controls as well as high-quality materials. This product could give a big impact to all the users as it makes life easier, less power consuming as well as saving more time. Customers also can enjoy different types of the coldness. For the potential commercialization, we expect to develop new features in our product such as subfans where there will be another mini fan behind the stand also inventing new products such as NEO Smart Umbrella with the aim to become the high-tech brand to all the consumers.